2019
DOI: 10.1001/jamanetworkopen.2019.0194
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Dependent Conditional Survival and Failure Hazard After Radiotherapy for Early-Stage Extranodal Natural Killer/T-Cell Lymphoma

Abstract: This cohort study assesses changes in survival probabilities and failure hazard after radiotherapy in adult patients with early-stage extranodal natural killer/T-cell lymphoma based on risk categories, previous survival, and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 52 publications
5
44
0
Order By: Relevance
“…Consistently in our recent analyses, [20][21][22][23] the risk of failure and death was high initially, but decreased dramatically over time in intermediate-risk/high-risk patients treated with non-ANT-based CT and RT, whereas it remained constantly low in low-risk patients primarily treated with RT. 20 Radiotherapy for elderly patients without risk factors (stage II, elevated LDH, ECOG score ≥ 2, PTI) achieved a very favorable OS equivalent to the age-matched and sex-matched general Chinese population. 21 These findings suggest that RT with or without CT is a viable treatment option for low-risk early-stage patients in the modern CT era.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Consistently in our recent analyses, [20][21][22][23] the risk of failure and death was high initially, but decreased dramatically over time in intermediate-risk/high-risk patients treated with non-ANT-based CT and RT, whereas it remained constantly low in low-risk patients primarily treated with RT. 20 Radiotherapy for elderly patients without risk factors (stage II, elevated LDH, ECOG score ≥ 2, PTI) achieved a very favorable OS equivalent to the age-matched and sex-matched general Chinese population. 21 These findings suggest that RT with or without CT is a viable treatment option for low-risk early-stage patients in the modern CT era.…”
Section: Discussionsupporting
confidence: 88%
“…[14][15][16][17][18][19] In recent pooled studies from the China Lymphoma Collaborative Group (CLCG), new CT regimens significantly improved survival compared with ANT-based regimens, regardless of stage and age. [20][21][22][23] However, RT remained an essential component of first-line therapy for early-stage patients, 22,23 even after complete response (CR) to asparaginase (ASP)-based CT. 24,25 Note, RT increased survival probability and decreased hazards of failure in a risk-dependent manner. [20][21][22]26 With the advent of new CT regimens, 11,[14][15][16][17][18][19] the survival benefit of CT in addition to RT in early-stage patients in different risk groups should be determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is an urgent requirement to identify patients at high risk of early progression who would benefit from innovative treatment strategies. Following the achievement of PFS24, research for ENKTCL survivors should focus on lessintensive surveillance, long-term treatment toxicity, quality of life, and other outcomes [34,37,38]. Previous studies, mainly using the randomized controlled trial (RCT) or real-world data, have demonstrated that the surrogate endpoints of EFS and PFS are strongly related to OS at both trial-and individual-level in different lymphoma subtypes [26-29, 32, 39-41].…”
Section: Discussionmentioning
confidence: 99%
“…CS denotes the probability of survival for an additional y years given an existing survival time of x years, which is calculated as CS(y|x)=S(x+y)/S(x). The concept of CS can extend to multiple endpoints, deriving conditional OS (COS), conditional DFS (CDFS), conditional LRRFS (CLRRFS), conditional DMFS (CDMFS) and conditional NPC‐SS (CNPC‐SS) [1,3,26]. For example, the 3‐year CDFS at 5 years demonstrates the probability of being disease‐free for an additional 3 years given an existing disease‐free time of 5 years.…”
Section: Methodsmentioning
confidence: 99%